Invasive Group A Streptococcus Infection in Children in Central Israel in 2012–2019. Issue 7 (July 2021) - Canetti, Michal; Carmi, Amit; Paret, Gideon; Goldberg, Lior; Adler, Amos; Amit, Sharon; Rokney, Assaf; Ron, Merav; Grisaru-Soen, Galia
Abstract : Background: Group A Streptococcus can cause serious and sometimes life-threatening disease in children. The past few years have witnessed a rise in invasive group A Streptococcus infection (iGASi) for unclear reasons. This study attempted to describe the epidemiology, the clinical and demographic characteristics and the outcomes associated with iGASi in hospitalized children in central Israel Methods: We retrospectively analyzed the medical records of children <18 years old discharged with a diagnosis of iGASi between January 2012 and December 2019. Clinical, laboratory and microbiologic data, and immunization status were retrieved. The patients were divided into severe and nonsevere groups based on their clinical presentation. The emm type was determined at the national reference center. Results: A total of 167 patients with 206 positive cultures for group A Streptococcus were identified. Hospitalizations for iGASi increased from 701 to 958 per 100, 000 admissions between 2012–2015 and 2016–2019, respectively, representing an increase of 37%. The majority of the isolates were from the otolaryngologic system followed by blood, deep soft tissue and respiratory sites. Uncomplicated mastoiditis was the most common diagnosis, followed by bacteremia. Pneumonia was the main diagnosis in the severe group (39.4%). Conclusions: The admissions because of iGASi in children <18 years old increased during the last 8 years. Surveillance systems and prospective studies should be conducted to expend our understanding of the epidemiology of iGASi in children, better assess the pathogenesis and specific risk factors and monitor changes in emm -type distribution. Abstract : Supplemental Digital Content is available in the text.